Analysts’ reliance on industry-level versus firm-specific information: Implications for information production - Choi, Hae Mi; Gupta-Mukherjee, Swasti (Journal of Banking & Finance, 2022)
Motivated by models of rational inattention, we study the information choices of sell-side analysts who face attention constraints in acquiring and processing costly information. We empirically examine analysts’ relative reliance on industry-level (i.e. macro) and firm-specific (i.e. micro) information in generating firms’ earnings forecasts. We find that analysts’ reliance on industry-level relative to firm-specific information decreases with available resources and their incentives to allocate effort towards firm-specific research. Specifically, analysts’ relative reliance on industry-level information increases with the number of firms and industries covered, while it decreases with brokerage size and experience. Analysts’ relative reliance on industry-level information decreases when they face more competition and cover firms with more career-related potential rewards for firm-specific research, such as large firms, and firms with high trading volume and institutional ownership. Moreover, analysts who rely relatively more on industry-level information issue less accurate but more frequent forecasts. Together, the evidence is consistent with analysts’ reliance on industry-level versus firm-specific information indicating a strategic allocation of effort among different aspects of information production, i.e. quality and quantity of earnings forecasts.